2015
DOI: 10.1016/j.enpol.2015.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Integrating global energy and climate governance: The changing role of the International Energy Agency

Abstract: Despite the long-recognized interlinkages between global energy consumption and climate change, there has historically been only limited policy interaction, let alone integration, between the two fields. This compartmentalization is mirrored in scholarship, where much research has focused on the fragmentation of, respectively, global energy and global climate governance, but only little has been said about how these fields might be integrated. Our analysis of the International Energy Agency's (IEA) changing ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(49 citation statements)
references
References 63 publications
0
48
0
1
Order By: Relevance
“…A second set of questions relates to the interplay between energy governance and related areas, in particular climate change (Fouquet, 2013;Heubaum and Biermann, 2015), water (Hussey and Pittock, 2012) and food security (Hendrix and Salehyan, 2012). The notion of a "resource nexus" captures the idea that these areas are all closely interconnected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A second set of questions relates to the interplay between energy governance and related areas, in particular climate change (Fouquet, 2013;Heubaum and Biermann, 2015), water (Hussey and Pittock, 2012) and food security (Hendrix and Salehyan, 2012). The notion of a "resource nexus" captures the idea that these areas are all closely interconnected.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally regarded as the "world's foremost multilateral energy organization" (Van de Graaf, 2015) and "the closest we have to a World Energy Organization" (Van de Graaf, 2013a). It should thus not come as a surprise that the IEA's evolving role and governance functions has received ample attention, both in the 1970s and 1980s and in recent years Colgan, 2009;Leverett, 2010;Kohl, 2010;Van de Graaf, 2012Lesage and Van de Graaf, 2013;Heubaum and Biermann, 2015;Colgan and Van de Graaf, 2015).…”
Section: Key International Organizationsmentioning
confidence: 99%
“…This observation has crossed over to the popular press: Leonhardt [94,95], Avent [4]. 27 Kobos et al [86], Horbach [70], Ahlborg [2], Boschma Capone [15], Heubaum and Biermann [69]. 28 Bosetti et al [16], Ek et al [49], Kahouli [81], Kalkuhl, Edenhofer and Lessmann [82,83], Lindman and Soderholm [98], Rubin [129], Lindahl et al [97].…”
Section: Governing the Climate Commonsmentioning
confidence: 99%
“…Principles for dealing with such a situation have been developed across a number of fields as diverse as financial portfolio analysis, 68 project management, 69 technology risk assessment, 70 Black Swan Theory, 71 military strategy 72 and space exploration. 73 Recommendations for building portfolios of assets are similar across these fields.…”
Section: Portfolio Analysismentioning
confidence: 99%
“…However, despite clear linkages, many have observed that in terms of global policy and governance, energy and climate change are separate fields (e.g. Gunningham, 2012;Heubaum & Biermann, 2015). For example, there is no single explicit mention of energy in the 2015 Paris Agreement on climate change (UNFCCC, 2015).…”
Section: Introductionmentioning
confidence: 99%